Discoid lupus erythematosus in childhood. A report of two cases. - Can, B.; Kavala, M.; Zindanci, İ.; Türkoğlu, Z.; Südoğan, S. (European Journal of Pediatric Dermatology, 2018)
Discoid lupus erythematosus (DLE) is an uncommon disease in childhood. DLE is characterized by the presence of discoid skin lesions without systemic involvement. The clinical hallmark of DLE is a discoid plaque with scarring, atrophy, follicular plugging, and scaling. Telangiectases and pigmentary changes are commonly present. DLE should be differentiated from systemic lupus erythematosus and neonatal lupus erythematosus. Here we present two new cases of childhood DLE.